Distortion product otoacoustic emissions: towards reliable and valid early identification and monitoring of hearing in adults receiving ototoxic medication - Petersen, Lucretia (Department of Health and Rehabilitation Sciences, 2023)
Background: Multidrug-resistant tuberculosis (MDR-TB) patients receive aminoglycosides as part of their treatment. These drugs are ototoxic, and can cause permanent damage to the cochlea, resulting in a debilitating hearing loss, which has a negative impact on an individual's quality of life. Early detection and management of an ototoxic hearing loss can minimise the impact of the hearing loss on the person's social, emotional, and vocational wellbeing. While patients with MDR-TB are often very ill, it might be ideal to use an objective test that does not require active participation from the patient. In this way, the reliability and validity of the test will not be affected by the patient's state. Distortion product otoacoustic emissions (DPOAEs) at 2f1-f2 are a viable option, as it evaluates cochlear function, specifically the outer hair cells, which are affected first by ototoxic medication. Method: This thesis used a sequential study design aimed to determine the DPOAE stimulus parameters that yield (a) the highest level and the most reliable, sensitive and specific DPOAEs reported in the literature, (b) the highest level and the most reliable DPOAEs in healthy, normally hearing adults, and (c) the most sensitive and specific DPOAEs in participants with MDR-TB patients receiving ototoxic medication. High frequency pure tone audiometry (defined in this thesis as frequencies > 8 kHz) was used as the gold standard. Descriptive statistics, the intraclass correlation coefficient, Pearson's correlation coefficient and mixed model analyses were used to analyse the data. Results: Systematic review: The results of the systematic review indicated an L1/L2 setting of 75/75 dB SPL and f2/f1 value from 1.20 to 1.22 yielded the highest level DPOAEs. The systematic review results for stimulus parameters that yielded the highest test-retest reliability, sensitivity and specificity were inconclusive. Preliminary study with healthy normal hearing participants: The results of the preliminary study in healthy, normal-hearing participants indicated that the highest levels of DPOAEs were elicited with L1/L2 intensity levels of 65/65 and 65/55 dB SPL, and f2/f1 ratios of 1.18, 1.20 and 1.22, as determined by mixed model analyses (p < 0.05). These same stimulus parameters yielded the most reliable DPOAEs in both ears, as determined by intraclass correlation coefficient analysis. Main study with healthy, normal-hearing participants: Descriptive statistics and mixed model analysis showed stimulus intensity levels L1/L2 of 65/55 dB SPL, and f2/f1 ratios of 1.18 and 1.20, elicited the largest DPOAEs. The ratio of 1.20 yielded the largest DPOAEs < 5000 Hz and f2/f1 ratio of 1.18 the largest DPOAEs ≥ 5000 Hz. The second highest DPOAE levels were elicit by L1/L2 = 65/65 dB SPL and f2/f1 = 1.18. The test-retest reliability in this sample was not influenced by changing the stimulus parameters, and DPOAEs were only unreliable at an f2 frequency of 8 000 Hz. Study in participants with MDR-TB: Results in participants with MDR-TB receiving ototoxic medication indicated that the highest levels of DPOAEs were elicited with L1/L2 = 65/55 and an f2/f1 ratio of 1.18 at f2 ≥ 5000 Hz, followed by 65/65 and 1.18. For f2 < 5000 Hz, stimulus intensities of L1/L2 = 65/55 and an f2/f1 ratio of 1.20 yielded the largest DPOAE levels. Relating to sensitivity and specificity, the stimulus parameter combination of 65/55 dB and 1.18 detected the highest number of ears with outer hair cell damage in participants with MDR-TB receiving ototoxic medication. Conclusion: It should be considered to use an f2/f1 ratio of 1.18 for f2 ≥ 5000 Hz and 1.20 for f2 < 5000 Hz when monitoring for ototoxicity, to assist with early identification of outer hair cell damage, in conjunction with high frequency pure tone audiometry. This finding needs to be confirmed in a larger sample of participants with MDR-TB receiving ototoxic medication.